Associations of older adults' excursions from home with health-related physical activity and sedentary behavior. (January 2021) - Fukushima, Noritoshi; Amagasa, Shiho; Kikuchi, Hiroyuki; Kataoka, Aoi; Takamiya, Tomoko; Odagiri, Yuko; Machida, Masaki; Oka, Koichiro; Owen, Neville; Inoue, Shigeru
Highlights: Fewer excursions from home by older adults were associated with being less active. Fewer excursions were also associated with more prolonged sedentary bout time. Associations of excursions with being active/sedentary may differ by urbanicity. Promoting excursions by older adults has considerable preventive-health potential. Abstract: Background: As people age, they spend more time in and around their domestic environments, within which opportunities for health-enhancing physical activity (PA) may be limited. We examined the associations of frequency of excursions from home with accelerometer-determined PA and the total and prolonged sedentary behavior (SB, sitting for ≥30 min) among community-dwelling older adults. Methods: Overall, 434 older adults (men, 57.1 %; age, 70–79 years) wore an accelerometer (HJA-350IT, Omron Healthcare) for 7 days. Time spent in SB, light-intensity PA (LPA), moderate-to-vigorous PA (MVPA), and prolonged SB bout (≥30 min) were calculated. Frequencies of excursions from home were categorized as 0−3, 4−5, and 6−7 days/week. Associations of excursions with PA and SB were tested by analysis of covariance adjusted for sociodemographic characteristics. Results: Frequencies were 14.3 %, 31.1 %, and 54.6 % for excursions 0−3, 4−5, and 6−7 days/week, respectively. For men, less frequent excursions from home were significantly associated with less MVPA and more total and prolonged SB times (estimated means [minutes/day]: MVPA, 32, 42, and 48; total SB, 589, 549, and 539; prolonged SB, 344, 288, and 265; respectively; p < 0.05). LPA was not statistically significant (p = 0.09). For women, less frequent excursions were significantly associated with all PA outcomes (SB: 536, 497, and 467; prolonged SB: 260, 213, and 204; LPA: 328, 363, and 379; MVPA: 36, 39, and 54, respectively). Conclusions: Among community-dwelling Japanese older adults, more frequent excursions from home were associated with more PA, less SB, and more-favorable SB patterns, suggesting a potential strategy for preventive-health initiatives.